The learning cost of interest rate reversals. - Ellison, M (Elsevier, 2006)
Many central banks in many time periods have sought to avoid interest rate reversals, but at present there is no good explanation of this phenomenon. Our analysis identifies a new learning cost associated with reversing the interest rate. In a standard monetary model with forward-looking expectations, data uncertainty and parameter uncertainty, a policy that frequently reverses the interest rate makes learning the key parameters of the model more difficult. Optimal monetary policy internalises this learning cost and therefore has a lower number of interest rate reversals.